2022
DOI: 10.1007/s10493-022-00686-y
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal patterns of oribatid mites across habitats and seasons

Abstract: Oribatid mites are tiny arthropods that are common in all soils of the world; however, they also occur in microhabitats above the soil such as lichens, mosses, on the bark of trees and in suspended soils. For understanding oribatid mite community structure, it is important to know whether they are dispersal limited. The aim of this study was to investigate the importance of oribatid mite dispersal using Malaise traps to exclude sole passive wind-dispersal. Oribatid mite communities were collected over a 3-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more prominent than in the environments of soils [60] and forests [61], which are also the study area of rocky desertification.…”
Section: Diversity Of Epilithic Moss Mites In Different Rock Desertif...mentioning
confidence: 99%
“…The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more The α-diversity, β-diversity and γ-diversity of mite communities are influenced by large-scale environmental factors, such as geographic location, natural hazards and climate [56][57][58] and are also limited by microhabitats such as lichens, mosses, bark and soil surfaces [59]. It was found that the number of individuals and family taxa of mites in the microhabitat of mosses was richer and the community characteristics were more prominent than in the environments of soils [60] and forests [61], which are also the study area of rocky desertification.…”
Section: Diversity Of Epilithic Moss Mites In Different Rock Desertif...mentioning
confidence: 99%
“…The variety in the number of bat species herein identified (i.e., 21 bat species belonging to 15 genera and 5 families) confirms the high biodiversity described in the Neotropical Region ( Willig and Selcer, 1989 ). Though an overall high ectoparasite infestation rate (42.5%) was recorded in sampled animals, the higher frequency of ectoparasites from Santa Cruz was probably due to the to the higher number of female bats captured from this area (37 vs 27), being the latter more prone to the parasitism ( Patterson et al, 2008 ; Presley and Willig, 2008 ), but also to the drier and milder climate of Santa Cruz that provides increased ectoparasite reproduction rates, as well as mammal infestations ( Adler et al, 2003 ; Rui and Graciolli, 2005 ; Lourenço and Palmerim, 2008 ; de Mendonça et al, 2020 ; Cordes et al, 2022 ). In addition, the higher detection of mites (91.6%, 44/48) than flies (6.2%, 3/48), along with the presence of co-infestation (i.e., tick larvae and flies) in a single individual, differ from previous reports, in which flies were the most abundant ectoparasites, often co-infesting bats, with the association streblid-spinturnicid species as the most common, especially in the Neotropical Region ( Szentiványi et al, 2019 ; Lourenço et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…A plausible explanation for this trend is the series of environmental changes preceding the wet period. After enduring alternating flood and dry conditions for several months, factors such as substrate moisture, salinity, and food availability undergo significant shifts across habitats [16,48,49]. In wetland ecosystems, terrestrial plant litter accumulates during dry spells and undergoes partial in-situ decomposition, enriching the humic material reservoir.…”
Section: Discussionmentioning
confidence: 99%